Evaluation of Compliance with the Runway Occupancy Time Standard at Soekarno-Hatta International Airport - Rosmayanti, Lina; Abimanyu, Yudha; Sonhaji, Imam; Faridan Juniawan, Ahmad (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
The research aims to calculate the runway occupancy time (ROT) at Soekarno-Hatta International Airport. ROTs are crucial in calculating the runway capacity, which can influence the time it takes for the aircraft to exit the runways after landing or enter a runway before takeoff. This may have an impact on the quantity of aircraft that utilize the runway for takeoffs and landings within an hour. The Runway Occupancy Time calculation model, which is the Doratask model in the Runway Capacity Calculation Manual, is employed in this study along with quantitative methodologies and questionnaires. The data collection techniques used are observations, documentation studies and interviews. The results of this study showed that the average ROT at Soekarno-Hatta International Airport was 95.36 seconds for ROTT and 54.63 seconds for the ROTL.